Fe3O4 quantum dots embedded in porous carbon microspheres for long-life lithium-ion batteries. (June 2019) - Liu, Yang; Dai, Yan; Jiang, Xiaobin; Li, Xiangcun; Yan, Zhijun; He, Gaohong
Abstract: We report here Fe3 O4 quantum dots embedded Fe3 O4 @C electrode materials via a facile micelle-colloid template method for pushing forward the Li-ion battery technology. To improve uniform dispersion of Fe3 O4 quantum dots (5–10 nm) and create macropores in the carbon matrix, ferric micelle colloids of CTA + X −1 Fe 3+ with chelate adsorption of ferric colloids on CTAB micelle corona by electrostatic attraction has been developed in a resin layer. Thus, nanocrystalline Fe3 O4 and graphitic carbon matrix are mutually formed from the same texture during the pyrolysis process, resulting in a tightly tangled carbon-Fe3 O4 hybrids. The conformable embedment of Fe3 O4 quantum dots in carbon matrix can effectively prevent its loss and alleviate local tension stress for volume variation during change-discharge process. The well structure-designed Fe3 O4 @C electrode materials deliver a stable capacity of 601 mA h g −1 at 2 A g −1 even after 800 cycles. This work provides a new strategy for design of transition-metal-oxide based electrode materials for long-life lithium-ion batteries. Graphical abstract: We report a novel Fe3 O4 @C electrode material by embedding Fe3 O4 quantum dots (5–10 nm) in porous carbon microspheres for long-life lithium-ion batteries. Ferric micelle colloids of CTA + X −1 Fe 3+ with chelate adsorption of ferric colloids on CTAB micelle corona by electrostatic attraction has been developed, resulting in uniform dispersion of Fe3 O4 quantum dots and formation of macropores in the carbon matrix. The conformable embedment of Fe3 O4 quantum dots in carbon matrix can effectively prevent its loss and alleviate local tension stress for volume variation during change-discharge process, resulting in a high cycling stability of the hybrids. This work provides a new strategy for design of transition-metal-oxide based electrode materials for long-life lithium-ion batteries.Image 1 Highlights: Fe3 O4 @C with conformably encapsulation of Fe3 O4 quantum dots in carbon matrix. Ferric micelle colloids of CTA + X −1 Fe 3+ has been developed in a resin layer. Crevices and pulverization of Fe3 O4 quantum dots within graphitic carbon matrix. Fe3 O4 @C delivers a capacity of 601 mA h g −1 at 2 A g −1 after 800 cycles.